Business Cluster and Entrepreneurship Growth in Nigeria: A Systematic Review. - Isiaka Mustapha; Zubairu Umaru Mustapha; Sakariyau Busra (Journal of Business and Behavioural Entrepreneurship, 2021)
The research in business clusters (BC) system of entrepreneurship development has increased in the recent year. A plethora of research has explored; entrepreneurship and urban growth, the entrepreneurial attitudes on the structure of support for entrepreneurship in an ecosystem, the effect of business clusters on firm performance and more recently, the dimension of agglomeration, institution and environment on business clusters. With the aid of Systematic Qualitative Assessment Techniques (SQAT), we review 79 business cluster journal articles published over the last 11 years (2010 – 2020) that sought to provide BC antecedent and impact on entrepreneurship and economy growth to provide a point for future research. Also, the review provides the geographic distribution, time distribution, underlying drivers of previous research, types and method of data collection used by these BC articles. Our findings shed light on the key themes including the evolution of BC, the impact of BC on the economy, application of BCs and the public policy maker roles. Furthermore, there is a dearth of BC research in Africa, South America and Australasia with most BC research are empirical and this represents gaps for future researchers to explore.